2005
DOI: 10.1016/j.neuron.2005.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Connecting the Navigational Clock to Sun Compass Input in Monarch Butterfly Brain

Abstract: Migratory monarch butterflies (Danaus plexippus) use a time-compensated sun compass to navigate to their overwintering grounds in Mexico. Although polarized light is one of the celestial cues used for orientation, the spectral content (color) of that light has not been fully explored. We cloned the cDNAs of three visual pigment-encoding opsins (ultraviolet [UV], blue, and long wavelength) and found that all three are expressed uniformly in main retina. The photoreceptors of the polarization-specialized dorsal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
232
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 187 publications
(246 citation statements)
references
References 43 publications
14
232
0
Order By: Relevance
“…In Drosophila (Wernet et al, 2003) and monarch butterflies (Sauman et al, 2005), the ommatidia of the DRA have a unique pattern of opsin expression compared to the main retina -this region contains ommatidia with rhabdoms specialized for polarization vision (Labhart and Meyer, 1999;Stalleicken et al, 2006). One possible explanation for the dramatically altered pattern of opsin mRNA expression we identified in the dorsal part of the L. rubidus eye is that it represents an expansion of the DRA.…”
Section: Rhabdoms Of the Main Retina Are Organized For Color Visionmentioning
confidence: 84%
See 4 more Smart Citations
“…In Drosophila (Wernet et al, 2003) and monarch butterflies (Sauman et al, 2005), the ommatidia of the DRA have a unique pattern of opsin expression compared to the main retina -this region contains ommatidia with rhabdoms specialized for polarization vision (Labhart and Meyer, 1999;Stalleicken et al, 2006). One possible explanation for the dramatically altered pattern of opsin mRNA expression we identified in the dorsal part of the L. rubidus eye is that it represents an expansion of the DRA.…”
Section: Rhabdoms Of the Main Retina Are Organized For Color Visionmentioning
confidence: 84%
“…Unlike the unusual BRh1 mRNA expression in the outer R3-8 photoreceptor cells of the L. rubidus dorsal eye, the typical lepidopteran expresses short wavelength opsin mRNAs only in the R1 and R2 cells (Kitamoto et al, 2000;Briscoe et al, 2003;White et al, 2003;Sauman et al, 2005). Closer inspection of UVRh, BRh1 and BRh2 expression in individual ommatidia indicated that these transcripts are also present in the R1 and R2 photoreceptor cells of both sexes (Fig.·4).…”
Section: Non-overlapping Expression Of Uvrh Brh1 and Brh2mentioning
confidence: 97%
See 3 more Smart Citations